#DocsOnTwitter: How Physicians use Social Media to Build Social Capital. Issue 1 (2nd January 2018) - Hanzel, Taylor; Richards, Jessica; Schwitters, Paige; Smith, Kirsten; Wendland, Kyle; Martin, Jamie; Keltgen, Jaciel
ABSTRACT: Using social capital theory, Augustana University healthcare marketing students examined how medical professionals utilize social media to further engage with their communities. The team selected Twitter as the social media network from which to collect data because of its popularity and ease of use. The sample was drawn from 1, 000 Twitter profiles that were retrieved from 24 keywords such as MD . A total of 3, 378, 285 tweets from this sample were collected and analyzed for content, use of hashtags, mobile device use, frequency, longevity, medical relevance, medical specialty, gender, and approximate age. This is an important first look, using Big Data, at how physicians parlay the popularity of social media to build social capital through sharing research with colleagues, connecting with patients and prospective patients, and extending their personal and employer brands to increasingly information-hungry and interactive consumers.